Blast-resistant rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Varieties of rainfed rice that are resistant to Blast, have high production potential, and are well adapted to African climates have been developed by plant breeders at the International Institute of Tropical Agriculture (IITA). Carried by fungi,...